-3(7n-4)=-36-5n

Simple and best practice solution for -3(7n-4)=-36-5n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(7n-4)=-36-5n equation:



-3(7n-4)=-36-5n
We move all terms to the left:
-3(7n-4)-(-36-5n)=0
We add all the numbers together, and all the variables
-3(7n-4)-(-5n-36)=0
We multiply parentheses
-21n-(-5n-36)+12=0
We get rid of parentheses
-21n+5n+36+12=0
We add all the numbers together, and all the variables
-16n+48=0
We move all terms containing n to the left, all other terms to the right
-16n=-48
n=-48/-16
n=+3

See similar equations:

| 2z+8/3=(z/4)+5 | | .4x=-6.4 | | 6(x+3)-4=x+9-10 | | 12(x-3)+18=6(20-3) | | -5x+2=13x+-160 | | -2b+5=-2(b+2)+7 | | 2x+3x+5=5x+5 | | H+£=y | | -8x+12=-5(8x+4) | | 321321+344.5x=333.64 | | 1/2(3w-8)=25 | | 49=11-2(8+3x) | | 2x16=21-7 | | -81=-41-9n | | 3(x-5)-10=2x-17 | | 3x(5x÷30)×2=7x+60 | | –19j+8j+–4=18 | | 12=17-p | | .7x+.2(40)=0.5(x+20) | | 5y+2+2y+9=12y-9 | | 6(x-9)=6x | | -(x+3)+3x=2(x+3) | | 15x+9=-2x+128 | | x-62=-40 | | -2(2-6n)+6n=9n-4 | | 6=50h-20 | | -r-26=-2(8+3r) | | x-35=17.5 | | 101-x=176 | | 1.2+.5x=4.2 | | 11x-65+25+25=180 | | (1/4)(6x+1)=8 |

Equations solver categories